2016
DOI: 10.1128/aac.00360-16
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Plasmids Carrying Multiple GES Variants

Abstract: e Five GES-producing Enterobacteriaceae isolates that displayed an extended-spectrum ␤-lactamase (ESBL) phenotype harbored two GES variants: GES-7 ESBL and GES-6 carbapenemase. In all isolates, the two GES alleles were located on the same integron that was inserted into an 80-kb IncM1 self-conjugative plasmid. Whole-genome sequencing suggested in vivo horizontal gene transfer of the plasmid along with clonal diffusion of Enterobacter cloacae. To our knowledge, this is the first description in Europe of cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…In 2016, Cuzon and colleagues reported an L/M plasmid carrying GES‐5 and GES‐6 on the same plasmid (Table ). This plasmid harbored additional ARGs, including aadA1 and sul 1; bla GES‐5 and bla GES‐6 were located on a class 1 integron, and both sides were flanked by IS 26 and IS 6100 . This pEB‐1 plasmid was compared with other L/M plasmids, pEL60 and pNDM‐OM, and similar characteristics were observed, except that the integration site of the ARGs array was different .…”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Cuzon and colleagues reported an L/M plasmid carrying GES‐5 and GES‐6 on the same plasmid (Table ). This plasmid harbored additional ARGs, including aadA1 and sul 1; bla GES‐5 and bla GES‐6 were located on a class 1 integron, and both sides were flanked by IS 26 and IS 6100 . This pEB‐1 plasmid was compared with other L/M plasmids, pEL60 and pNDM‐OM, and similar characteristics were observed, except that the integration site of the ARGs array was different .…”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 99%
“…This plasmid harbored additional ARGs, including aadA1 and sul 1; bla GES‐5 and bla GES‐6 were located on a class 1 integron, and both sides were flanked by IS 26 and IS 6100 . This pEB‐1 plasmid was compared with other L/M plasmids, pEL60 and pNDM‐OM, and similar characteristics were observed, except that the integration site of the ARGs array was different . In South Africa, bla GES‐5 was reported on an IncQ plasmid but still within a class 1 integron, with an additional aadA4 on an integron mobilization unit …”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 99%
“…A number of mercury‐resistant bacterial strains were isolated from Daroghawala dumping site soil, with strain DWH4 demonstrating resistance to mercury at concentration as high as 60 mg HgCl 2 l −1 . Strain DWH4 was identified as E. cloacae , which has been previously reported as a mercury‐resistant soilborne bacterium with an identified mer ‐like chromosomal gene sequence (Cuzon et al ; Mobeen and Latif ; Rahman et al ). A 527‐bp merR ‐like gene and associated promoter were subsequently identified that showed 99% similarity to merR ‐like sequences from E. agglomerans , A. calcoaciticus , P. aeruginosa and another E. cloacae strain (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…RLU; relative light units. (Cuzon et al 2016;Mobeen and Latif 2016;Rahman et al 2017). A 527-bp merR-like gene and associated promoter were subsequently identified that showed 99% similarity to merR-like sequences from E. agglomerans, A. calcoaciticus, P. aeruginosa and another E. cloacae strain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance of DNA as biological target, highly sensitive and specific determination of sequence‐specific DNA is crucial in clinical diagnosis, environmental monitoring, gene profiling and pathogen detection . In recent years, a variety of techniques have been used for DNA detection, such as DNA microarray , chemiluminiscence ,, colorimetry , surface plasmon resonance , electrochemistry , and so on. Among these techniques, the electrochemical techniques have received great interests owing to its superior characteristics of rapid response, low‐cost, small‐size, simple operation, and good selectivity .…”
Section: Introductionmentioning
confidence: 99%